Broiler Farms and Carcasses Are an Important Reservoir of Multi-Drug Resistant Escherichia coli in Ecuador - Ortega-Paredes, David; de Janon, Sofía; Villavicencio, Fernando; Ruales, Katherine Jaramillo; De La Torre, Kenny; Villacís, José E.; Wagenaar, Jaap A.; Matheu, Jorge; Bravo-Vallejo, Camila; Fernández-Moreira, Esteban; Vinueza-Burgos, Christian (Frontiers in Veterinary Science, 2020)
Antimicrobial resistance (AMR) is a major health threat for public and animal health in the 21st century. In Ecuador, antibiotics have been used by the poultry industry for decades resulting in the presence of multi-drug resistant (MDR) bacteria in the poultry meat production chain, with the consequent risk for public health. This study evaluated the prevalence of ESBL/AmpC and mcr genes in third-generation cephalosporin-resistant Escherichia coli (3GC-R E. coli) isolated from broiler farms (animal component), broiler carcasses (food component), and human enteritis (human component) in Quito-Ecuador. Samples were collected weekly from November 2017 to November 2018. For the animal, food and human components, 133, 335 and 302 samples were analyzed respectively. Profiles of antimicrobial resistance were analyzed by an automated microdilution system. Resistance genes were studied by PCR and Sanger sequencing. From all samples, 122 (91.7%), 258 (77%) and 146 (48.3%) samples were positive for 3GC-R E. coli in the animal, food and human components, respectively. Most of the isolates (472/526, 89.7%) presented MDR phenotypes. The ESBL blaCTX-M-55, blaCTX-M-3, blaCTX-M-15, blaCTX-M-65, blaCTX-M-27 and blaCTX-M-14 were the most prevalent ESBL genes while blaCMY-2 was the only AmpC detected gene. The mcr-1 gene was found in 20 (16.4%), 26 (10.1%) and 3 (2.1%) of isolates from animal, food, and human components, respectively. The implication of poultry products in the prevalence of ESBL/AmpC and mcr genes in 3GC-R must be considered in surveillance of antimicrobial resistance.